Quantification of root water uptake in soil using X-ray Computed Tomography and image based modelling - Daly, Keith R.; Tracy, Saoirse R.; Crout, Neil M.J.; Mairhofer, Stefan; Pridmore, Tony P.; Mooney, Sacha J.; Roose, Tiina (Wiley, 2017)
Spatially averaged models of root-soil interactions are often used to calculate plant water uptake. Using a combination of X-ray Computed Tomography (CT) and image based modelling we tested the accuracy of this spatial averaging by directly calculating plant water uptake for young wheat plants in two soil types. The root system was imaged using X-ray CT at 2, 4, 6, 8 and 12 days after transplanting. The roots were segmented using semi-automated root tracking for speed and reproducibility. The segmented geometries were converted to a mesh suitable for the numerical solution of Richards’ equation. Richards’ equation was parameterised using existing pore scale studies of soil hydraulic properties in the rhizosphere of wheat plants. Image based modelling allows the spatial distribution of water around the root to be visualised and the fluxes into the root to be calculated. By comparing the results obtained through image based modelling to spatially averaged models, the impact of root architecture and geometry in water uptake was quantified. We observed that the spatially averaged models performed well in comparison to the image based models with <2% difference in uptake. However, the spatial averaging loses important information regarding the spatial distribution of water near the root system.